Potential Application of Ascorbic Acid, Citric Acid and Oxalic Acid for Browning Inhibition in Fresh-Cut Fruits and Vegetables - Weerayuth SUTTIRAK; Supranee MANURAKCHINAKORN (Walailak Journal of Science and Technology, 2011)
The market for fresh-cut fruits and vegetables has grown rapidly in recent decades as a result of their freshness, convenience, and human health benefits. However, fresh fruits and vegetables deteriorate very rapidly after processing, especially cut-surface browning resulting from wound-induced physiological and biochemical changes. The application of antibrowning agents is one of the most effective methods for controlling the enzymatic browning reaction in fresh-cut fruits and vegetables. This article reviews the use of nature identical antibrowning agents, which are generally recognized as safe (GRAS) including ascorbic acid, citric acid and oxalic acid for preventing browning in fresh-cut fruits and vegetables. Factors affecting inhibitory efficiency of the antibrowning agents and synergistic effects of the mixtures in various fresh-cut fruits and vegetables are presented.